PS-R06-8: AMLODIPINE WELL RESPONDED TO HYPERTENSION ALONG WITH HEADACHE IN PATIENT UNDERGOING WHOLE BRAIN RADIATION THERAPY (CASE REPORT). (January 2023) - Ozeki, Rie; Sai, Hyonmi; Iijima, Kotaro; Watanabe, Junichiro; Saito, Mitsue
Abstract : Objective: According to the current treatment guideline for breast cancer issued by Japanese Breast Cancer Society, surgery or stereotactic radiotherapy is recommended for patients with solitary brain metastasis (BM), while whole brain radiotherapy (WBRT) is recommended for patients with multiple BMs. Common treatment-related toxicities during radiotherapy include fatigue, drowsiness, alopecia, headache, nausea, or vomiting, however, elevation of blood pressure has not been reported. We report a case of headache due to high blood pressure during WBRT. Case: A 5X-year female was diagnosed as HER2-positive operable left breast cancer underwent radical mastectomy followed by adjuvant chemotherapy including one-year trastuzumab. Three years after surgery she was diagnosed as having cancerous pleurisy, cancerous pericarditis, and multiple bone metastases. The patient received 6 cycles of trastuzumab, pertuzumab and docetaxel and 5 cycles of trastuzumab and pertuzumab. She noticed chronic headache and magnetic resonance imaging of the brain showed metastases to the right frontal lobe and left cerebellum. She was hospitalized and underwent WBRT. She received corticosteroid and glycerin-fructose injection to reduce the intracranial pressure (ICP) along with WBRT. On the 10th day of hospitalization, she complained severe headache with numerical rating scale (NRS) of 6. While an analgesic was not effective, elevated blood pressure (160/80 mmHg) since admission was suspected as a cause of headache. High-dose amlodipine at the dose of 10 mg was prescribed and the patient well responded to amlodipine as blood pressure of 130/70 mmHg and headache was relieved. Discussion: In patients with BMs, headache is common symptom due to elevate ICP or leptomeningeal dissemination. However, analgesic and ICP relief therapy did not work in this case. Guidelines for the management of hypertension 2019 (JSH 2019) define hypertension as 140/90 mmHg or higher, and in low-risk cases without underlying disease, non-pharmacologic therapy is recommended. Ultimately, the use of a calcium channel blockers resulted in a decrease in blood pressure and improvement in headache. It is possible that the headache was caused by increased sympathetic nerve activity via ischemia in the brainstem due to increased ICP, such as in brain tumors, which can lead to hypertension. Amlodipine is recommended for patients with chronic cerebrovascular disease because of its long acting and slow onset of effect, as well as its ability to protect organ blood flow. Conclusion: This case revealed hypertension may be the cause of headaches during WBRT, in which case amlodipine was effective.